A patient with reflex myoclonus and muscle rigidity: "jerking stiff-man syndrome". Issue 12 (December 1980) - Leigh, P N; Rothwell, J C; Traub, M; Marsden, C D
Abstract : A patient with progressive muscular rigidity associated with reflex myoclonus is described. The muscular rigidity was predominantly axial, and the myoclonic jerks affected axial and leg muscles. Jerks occurred either spontaneously, or in response to touch to the perioral region, or to stretch of head and neck muscles. Physiological investigations suggested that the myoclonus originated in the medulla and was mediated by fast-conducting pathways upwards through the brainstem and down the spinal cord. The relationship of this condition to other types of muscular rigidity with and without myoclonus is discussed.